Firm's environmental performance: a review of their determinants - Hojat, Amir Hossein Montazer; Abdul Rahim, Khalid; Lee, Chin (Science Publications, 2010)
Problem statement: The role of environment in global economic development is vital since it is the life-support system providing sources of food and water, pleasant surroundings and sceneries and transportation lines. Firms’ environmental performances are of high interest in worldwide environmental protection. Approach: Many factors affect firms’ environmental performance. Some of these are of external origin while others are of the internal ones. Several empirical studies have sought to identify these factors. Most of the studies, however, had analyzed merely one of the determinants of the environmental performance neglecting the others. Based on a review of fifty related studies, this research identified and reviewed the effects of three major determinants of firms’ environmental performance. Results: The results suggested that using market-based instruments and command-and-control approach to control pollution does not and should not prevent other factors from being considered. Just complying with the regulations was not sufficient to ensure prevention of environmental degradation. Moreover, the public and private costs of these methods of environmental protection were significant. In this study also the effected of voluntary actions doing by Firms were analyzed. Our findings showed that it is still unclear whether or not these actions lead to an improvement in firms’ environmental performance. Most previous studies on the effects on firms’ environmental performances of voluntary actions were not unanimous. Conclusion: The study also considered the effects on firms’ environmental performance of managerial attitudes. It followed that a logical development in the economic literature could be realized by analyzing the effects on firms’ environmental performance of managerial attitudes. In addition, although firms’ characteristics had been incorporated in the majority of relevant studies in the past, they present mixed conclusions. In fact, in order to make a proper policy, it is recommended that firms’ environmental performance be comprehensively considered, that is together with its all determinants.